Challenges of climate and environmental change / edited by Awadesh Kumar Singh - "Singh, Awadesh Kumar (ed.)" (New Delhi, 2012)
For some time, science has predicted that the planet is vulnerable to global warming caused by rising levels of carbon dioxide and other greenhouse gases in the atmosphere. Those that live in cold regions might feel that a little global warming would be desirable, but any significant change in our climate will result in losers as well as winners. The regions which may benefit often have few inhabitants while many heavily populated and highly-developed areas will suffer. Some may become completely uninhabitable. Change at this scale will be extremely stressful and expensive. The problem has its origins in the way life evolved on earth. The conditions necessary for life in the biosphere are the result of a complex set of delicately balanced systems which are still poorly understood. The atmospheric composition that permits life to exist was itself created in part by the action of the first living things. The earliest plants removed carbon dioxide from the atmosphere and added oxygen, making animal life possible.
Keywords: Climate change